Lateral Flow Immunoassay - Wong, Raphael C. (Springer, 2017)
Evolution in Lateral Flow–Based Immunoassay Systems. Market Trends in Lateral Flow Immunoassays. aterial Platform for the Assembly of Lateral Flow Immunoassay Test Strips. Antibodies: Key to a Robust Lateral Flow Immunoassay. Colloidal Gold and Other Labels for Lateral Flow Immunoassays. ....